Montreal's Square Mile: the making and transformation of a colonial metropole - Anastakis, Dimitry; Kirkland, Elizabeth; Nerbas, Don (University of Toronto Press, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

L'émergence et la transformation des interfaces ville-industrie: Le cas de la planification urbaine d'Assomption Sud-Longue-Pointe à Montréal - Lambert, Olivier (Université du Québec à Montréal, 2024)
Keywords: Longue-Pointe

Passé et avenir d'une rivière montréalaise - Legault, Louise (Histoire Québec, 2024)
Keywords: Lachine; Lachine (canal); Pollution; Égouts

Le mystère urbain de Crawford Park. Des origines à la Dépression- (Partie 1) - Voisine, John (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2023)
Keywords: Quartiers; Verdun

Évolution du village de Saint-Jean-Baptiste - Deschambault, Gabriel (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2022)
Keywords: Saint-Jean-Baptiste (village); Villages

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

Behind Strong Palings: Producing Knowledge in the Modern City at Montreal’s Emigrant Sheds, 1832-1852 - Horner, Dan (Urban History Review / Revue d'histoire urbaine, 2022)
Keywords: Choléra; Épidémies

Aux origines du village de Saint-Jean-Baptiste, 1850-1861 - Robert, Jean-Claude (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2022)
Keywords: Saint-Jean-Baptiste (village); Villages

1844-1849. Montréal, the New Seat of Government - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Champ-de-Mars; Fonctionnaires; Gouverneurs; Monklands; Palais de justice; Parlement; Ramezay (château de)

Railways and the Urban Soundscape: Montreal, 1850s-1950s - Rudy, Jarrett; Fahrni, Magda; Kenny, Nicolas (Urban History Review / Revue d'histoire urbaine, 2022)
Keywords: Chemins de fer; Paysages

The Goode House (The Westmount Historian, 2021)
Keywords: Conservation; Famille; Jardins; Patrimoine

Un territoire à habiter et à aménager (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Keywords: Ahuntsic; Cartierville; Logement; Quartiers; Sault-au-Récollet

Quand le temps s'arrête: une promenade dans le jardin de la maison Goode / Window to the Past: A Walk in the Garden of the Goode House - Adib, Danièle; Crépeau, Antoine (The Westmount Historian, 2021)
Keywords: Jardins

1800 to 1830. Montréal, Building British Metropolis - Robert, Jean-Claude (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne’s Market and the Parliament of the Province of Canada, 2021)
Keywords: Métropole; Port

De 1800 à 1830. Montréal, jeune métropole britannique - Robert, Jean-Claude (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Métropole; Port

1844-1849. Montréal, nouveau siège du gouvernement - Roy, Alain (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Champ-de-Mars; Fonctionnaires; Gouverneurs; Monklands; Palais de justice; Parlement; Ramezay (château de)

De part et d'autre de la Petite rivière. Montréal naît et grandit - Stewart, Alan (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Faubourgs; Fortifications; Forts

On Both Shores of the Little River. Montréal Emerges and Evolves - Stewart, Alan (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne’s Market and the Parliament of the Province of Canada, 2021)
Keywords: Faubourgs; Fortifications; Forts

La mutation vers un espace urbain moderne. Le projet de démantèlement des fortifications de Montréal - Beauchamp-Monfette, Joel (Cap-aux-Diamants, 2020)
Keywords: Fortifications

Le canal de Lachine: un paysage en constant mouvement - Paradis, Matthieu; Gelly, Alain (Histoire Québec, 2020)
Keywords: Lachine (canal); Paysages

1840-1912: De la montée du Sault à la rue Lajeunesse: sept décennies de chemins de barrières... et quelques incendies - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2019)
Keywords: Incendies; Routes; Rues

"To muse within these peaceful portals": Urban Space, Public Order, and the Makings of Montreal’s Viger Square, 1818-1870 - Horner, Dan (Violence, Order, and Unrest: A History of British North America, 1749-1876, 2019)
Keywords: Carré Viger; Marchés; Places publiques; Squares

Commerces du Plateau: d'hier à aujourd'hui (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2018)
Keywords: Alimentation; Artisans; Bijouterie; Chaussure; Commerce de détail; Magasins; Mont-Royal (rue); Plateau Mont-Royal; Quartiers; Quincaillerie; Rues; Saint-Denis (rue); Saint-Laurent (rue); Épicerie

The Modern City: 1840-1890 - Fougères, Dany (Montreal: The History of A North American City, 2018)
Keywords: Charte; Conseillers municipaux; Maires; Parcs; Places publiques; Quartiers; Saint-Antoine; Saint-Jacques; Saint-Laurent (quartier); Saint-Louis; Sainte-Anne; Sainte-Marie; Voirie; Élections

Montreal Old Cemeteries - MacLeod, Roderick (Montreal: The History of A North American City, 2018)
Keywords: Cimetières

Mount Royal: The Top of the Island - MacLeod, Roderick (Montreal: The History of A North American City, 2018)
Keywords: Mont Royal; Mont-Royal (parc); Parcs

De siège du gouvernement à capitale éphémère: Kingston, Montréal et le passage à l’État libéral moderne (1838–1849) - Roy, Alain (Urban History Review / Revue d'histoire urbaine, 2018)
Keywords: Gouverneurs; Parlement

Montréal, par rues et par ruelles - Archambault-Malouin, Diane (Histoire Québec, 2017)
Keywords: Rues; Toponymie

Les tanneries de Saint-Henri: de Jean-Talon à l'échangeur - Giasson, Guy (Histoire Québec, 2017)
Keywords: Artisans; Fourrure; Quartiers; Saint-Henri; Tannerie

Sound, Deindustrialization, and Gentrification: The Changing Aural Landscape of Pointe-Saint-Charles - Luderowski, Muriel (Université Concordia, 2017)
Keywords: Chemins de fer; Grand Tronc; Pointe-Saint-Charles; Quartiers

Beautiful Cities - Weinberg, Paul (Canada's History, 2017)
Keywords: Mont-Royal (parc)

Une ville fortifiée - Bélanger, Christian (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Fortifications; Forts

From desintegration to reinterpretation: urban design in Montreal, 1950-2014 - Racine, François (City as organism: new visions for urban life, 2016)
Keywords: Cartes et plans

Dans le jardin des sulpiciens, seigneurs de l'île - Vaillancourt, Pascale (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Communautés religieuses; Jardins; Sulpiciens

Des milieux de vie animés dans une ville en transformation rapide - Linteau, Paul-André (Quartiers disparus: Red Light, Faubourg à M'lasse, Goose Village, 2014)
Keywords: Quartiers

Quartiers disparus: Red Light, Faubourg à M'lasse, Goose Village - Linteau, Paul-André; Charlebois, Catherine (Les Éditions Cardinal, 2014)
Keywords: Drapeau, Jean; Faubourgs; Logement; Maires; Quartiers

Forme et sens des squares victoriens montréalais dans le contexte de développement de la métropole (1801-1914). 2 tomes - Cha, Jonathan (Université du Québec à Montréal, Institut national de la recherche scientifique et Institut d'urbanisme de Paris - Université Paris-Est, 2013)
Keywords: Squares

Forme et sens des squares victoriens montréalais dans le contexte de développement de la métropole (1801-1914). Volume II - Cha, Jonathan (Université du Québec à Montréal, Institut national de la recherche scientifique et Institut d'urbanisme de Paris - Université Paris-Est, 2013)
Keywords: Squares

Les jardins d'agrément en Nouvelle-France. Étude historique et cartographique - Fortier, Marie-Josée (Les Éditions GID, 2012)
Keywords: Jardins

La ville moderne, 1840-1890 - Fougères, Dany (Histoire de Montréal et de sa région, 2012)
Keywords: Charte; Conseillers municipaux; Maires; Parcs; Places publiques; Quartiers; Saint-Antoine; Saint-Jacques; Saint-Laurent (quartier); Saint-Louis; Sainte-Anne; Sainte-Marie; Voirie; Élections

Metropolitan Natures: Environmental Histories of Montreal - Castonguay, Stéphane; Dagenais, Michèle (University of Pittsburgh Press, 2011)

At the Source of a New Urbanity: Water Networks and Power Relations in the Second Half of the Nineteenth Century - Dagenais, Michèle (Metropolitan Natures: Environmental Histories of Montreal, 2011)
Keywords: Aqueduc

Surface Water in the Early Nineteenth Century - Fougères, Dany (Metropolitan Natures: Environmental Histories of Montreal, 2011)
Keywords: Aqueduc; Égouts

City Streets as Environmental Grid: The Challenge of Private Uses and Municipal Stewardship - Olson, Sherry (Metropolitan Natures: Environmental Histories of Montreal, 2011)
Keywords: Rues

Hidden Water in the Landscape: The Covered Reservoirs of Mount-Royal - Ross, Susan M. (Metropolitan Natures: Environmental Histories of Montreal, 2011)
Keywords: Aqueduc; Mont Royal

The Urbanization of Nature: Water Networks and Green Spaces in Montreal - Dagenais, Michèle (Method and Meaning in Canadian Environmental History, 2009)
Keywords: Aqueduc; Parcs; Égouts

Reconstruire Montréal, rebâtir sa fortune - Dufaux, François; Olson, Sherry (Revue de Bibliothèque et Archives nationale du Québec, 2009)
Keywords: Faubourgs; Logement

L'organisation spatiale du corridor du canal de Lachine au XIXe siècle - Desjardins, Pauline (Association des archéologues du Québec, 2006)
Keywords: Lachine (canal)

Évaluation du patrimoine urbain: arrondissement d'Anjou - Service de la mise en valeur du territoire et du patrimoine (Ville de Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Anjou; Arrondissements; Patrimoine

Évaluation du patrimoine urbain: arrondissement de Dollard-Des-Ormeaux - Roxboro - Service de la mise en valeur du territoire et du patrimoine (Ville de Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Dollard des Ormeaux; Patrimoine

Évaluation du patrimoine urbain: arrondissement de Kirkland - Service de la mise en valeur du territoire et du patrimoine (Ville de Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Patrimoine

Évaluation du patrimoine urbain: arrondissement de Montréal-Nord - Service de la mise en valeur du territoire et du patrimoine (Ville de Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Montréal-Nord; Patrimoine

Évaluation du patrimoine urbain: arrondissement de Rivière-des-Prairies - Pointe-aux-Trembles - Montréal-Est - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Montréal-Est; Patrimoine; Pointe-aux-Trembles; Rivière-des-Prairies

Évaluation du patrimoine urbain: arrondissement de Saint-Léonard - Service de la mise en valeur du territoire et du patrimoine (Ville de Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Patrimoine; Saint-Léonard

Évaluation du patrimoine urbain: arrondissement de Verdun - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Patrimoine; Verdun

Évaluation du patrimoine urbain: arrondissement de Ville-Marie - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Patrimoine; Ville-Marie (arrondissement)

Cimetière Notre-Dame-des-Neiges - Bisson, Pierre-Richard; Brodeur, Mario; Drouin, Daniel (Beaux livres Henri Rivard, 2004)
Keywords: Cimetières; Notre-Dame-des-Neiges (cimetière)

Les magasins-entrepôts de Montréal, 1850 à 1880 : formes et fonctions commerciales. Un nouveau regard - Burgess, Joanne; Lauzon, Gilles (Les territoires de l’entreprise / The Territories of Business, 2004)
Keywords: Magasins

Les faubourgs et leur évolution du XVIIIe siècle au milieu du XIXe siècle. Étude comparée d’Angers et de Montréal - Freney, Sylvie (Université du Québec à Montréal et Université d'Angers, 2004)
Keywords: Faubourgs

Muddy Shore to Modern Port: Redimensioning the Montréal Waterfront Time-Space - Gilliland, Jason A. (The Canadian Geographer / Le Géographe canadien, 2004)
Keywords: Paysages; Port

Promenade verdunoise: un aperçu - Harton, Denis (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2004)
Keywords: Quartiers; Rues; Verdun; Villages

The Settlement and Rural Domestic Architecture of Côte Saint-Antoine, 1675-1874 - MacKinnon, Janet S. (Université de Montréal, 2004)
Keywords: Côtes; Logement

Spécial patrimoine bâti (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2003)
Keywords: Bourgeoisie; Logement; Patrimoine; Quartiers; Rues; Verdun

Le rôle de la côte dans la formation de la grille de rues, sur l'île de Montréal, incluant Verdun - Harton, Denis (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2003)
Keywords: Côtes; Rues

The Road to Terrace Bank: Land Capitalization, Public Space, and the Redpath Family Home, 1837-1861 - Macleod, Roderick (Journal of Canadian Historical Association / Revue de la Société historique du Canada, 2003)
Keywords: Redpath (famille); Redpath, John

The Creative Destruction of Montreal: Street Widenings and Urban (Re) Development in the Nineteenth Century - Gilliland, Jason (Urban History Review / Revue d'histoire urbaine, 2002)
Keywords: Rues; Voirie

Pure Water in the City. Covering the Reservoirs on Mount Royal - Ross, Susan Martha (Université de Montréal, 2002)
Keywords: Aqueduc; Côte-des-Neiges; Mont Royal

Outdoor Play Areas for Children in High-Density Housing in Montreal - Aggarwal, Monica (Université McGill, 2001)
Keywords: Enfants; Parcs; Plateau Mont-Royal; Quartiers

Des rues et des hommes : les commencements des politiques publiques locales en matière de travaux publics à Montréal, 1796-1840 - Fougères, Dany (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2001)
Keywords: Rues; Voirie

Redimensioning Montreal: Circulation and Urban Form, 1846-1918 - Gilliland, Jason A. (Université McGill, 2001)
Keywords: Incendies; Port; Rues

A New World from Two Old Ones: the Evolution of Montreal's tenements, 1850-1892 - Dufaux, François (Urban Morphology, 2000)
Keywords: Logement

Une problématique pour une histoire des infrastructures urbaines à travers le cas de Montréal (1845-1960) - Gagnon, Robert; Fougères, Dany; Trépanier, Michel (Technology and Engineering, 2000)
Keywords: Aqueduc; Transport en commun; Égouts

Manufacturing Montreal. The Making of an Industrial Landscape, 1850-1930 - Lewis, Robert D. (John Hopkins University Press, 2000)
Keywords: Banlieue; Quartiers; Saint-Henri; Sainte-Anne

Les fondements du plan directeur. Volume 1 - Cimetière Notre-Dame-Des-Neiges (1999)
Keywords: Cimetières; Notre-Dame-des-Neiges (cimetière)

L'organisation spatiale du corridor du Canal de Lachine au 19e siècle - Desjardins, Pauline (Université de Montréal, 1999)
Keywords: Lachine (canal)

Place d'Youville à Montréal: évolution des modes de vie aux abords de la rivière Saint-Pierre entre 1775 et 1838 - Roy, Christian (Archéologiques, 1999)
Keywords: Artisans; Youville (place d')

Human Scale in the Urban Design of Montreal Residential Developments - Lucic, Katija (Université McGill, 1995)
Keywords: Anjou; Banlieue; Centre-sud (quartier); Quartiers; Rues; Squares

La maison et son environnement - Lambert, Phyllis (Montréal, ville fortifiée au XVIIIe siècle, 1992)

Le démantèlement des fortifications: vers une nouvelle forme urbaine - Lambert, Phyllis (Montréal, ville fortifiée au XVIIIe siècle, 1992)
Keywords: Fortifications

Removing the Fortifications: Toward a New Urban Form - Lambert, Phyllis (Opening the Gates of Eighteenth-Century Montréal, 1992)
Keywords: Fortifications

The House and Its Environment - Lambert, Phyllis (Opening the Gates of Eighteenth-Century Montréal, 1992)

Montréal, du faubourg au quartier (ou l'histoire véridique du faux frère siamois) - Lavigne, Gilles (Montréal: tableaux d'un espace en transformation, 1992)
Keywords: Faubourgs; Quartiers

Industry and Space: the Making of Montreal's Industrial Geography, 1850-1918 - Lewis, Robert D. (Université McGill, 1992)
Keywords: Banlieue; Quartiers; Saint-Henri; Sainte-Anne

Étude sur le patrimoine du square Saint-Louis et de ses abords. Rapport final - Consaur (s. éd., 1991)
Keywords: Patrimoine; Places publiques; Squares

Le plan Phillips: un projet urbain exemplaire de la mi-XIXe siècle à Montréal - Bertol Icart, Michèle (Université de Montréal, 1990)

Les parcs de Montréal. Des origines à nos jours - Laplante, Jean de (Éditions du Méridien, 1990)
Keywords: Parcs; Squares

Le potentiel archéologique du site du moulin Fleming, LaSalle - Savard, Mario; Côté, Robert (Groupe de recherches en histoire du Québec rural, 1989)
Keywords: Arrondissements; LaSalle; Meunerie

CHARLAND, LOUIS - Langelier, Gilles (Dictionnaire biographique du Canada, 1983)

L'urbanisation et le développement de l'habitation à St-Henri dès sa naissance jusqu'en 1939 - Wahba-Labib, Samia (Université de Montréal, 1982)
Keywords: Logement; Quartiers; Saint-Henri

Creation of an Early Victorian Suburb in Montreal - Hanna, David B. (Urban History Review / Revue d'histoire urbaine, 1980)
Keywords: Banlieue; Golden Square Mile; Logement; Quartiers

Industrial Land Use in Urban Areas with Special Reference to Montreal - Sharma, Brajesh Chander (Université McGill, 1971)